Crustal shear velocity structure in the Southern Lau Basin constrained by seafloor compliance. Issue 5 (30th May 2016) - Zha, Yang; Webb, Spahr C.
Abstract: Seafloor morphology and crustal structure vary significantly in the Lau back‐arc basin, which contains regions of island arc formation, rifting, and seafloor spreading. We analyze seafloor compliance: deformation under long period ocean wave forcing, at 30 ocean bottom seismometers to constrain crustal shear wave velocity structure along and across the Eastern Lau Spreading Center (ELSC). Velocity models obtained through Monte Carlo inversion of compliance data show systematic variation of crustal structure in the basin. Sediment thicknesses range from zero thickness at the ridge axis to 1400 m near the volcanic arc. Sediment thickness increases faster to the east than to the west of the ELSC, suggesting a more abundant source of sediment near the active arc volcanoes. Along the ELSC, upper crustal velocities increase from the south to the north where the ridge has migrated farther away from the volcanic arc front. Along the axial ELSC, compliance analysis did not detect a crustal low‐velocity body, indicating less melt in the ELSC crustal accretion zone compared to the fast spreading East Pacific Rise. Average upper crust shear velocities for the older ELSC crust produced when the ridge was near the volcanic arc are 0.5–0.8 km/s slower than crust produced at the present‐day northern ELSC, consistent with a more porous extrusive layer. Crust in the western Lau Basin, which although thought to have been produced through extension and rifting of old arc crust, is found to have upper crustal velocities similar to older oceanic crust produced at the ELSC. Key Points: Crustal shear velocity models in the Lau Basin inverted from seafloor compliance Upper crustal velocity along ELSC increases with ridge‐arc distance Sediment thickens asymmetrically on two sides of ridge